Development of Traffic Noise Prediction Model in an Educational Urban Area - Al-Mosawe, Hasan Mosa; Alobaydi, Dhirgham; Albayati, Amjad (Salehan Institute of Higher Education, 2018)
This paper studies the problem of noise pollution on the roads of the campus of University of Baghdad in Baghdad, Iraq. Due to the continuous redevelopment process conducted on the masterplan of the university, the noise levels have significantly impacted the education environment. The purpose of this paper was thus to study the sources caused and maximized the noise levels at the campus and also formulate a prediction model, identified the guidelines used for designing or developing future campus masterplans. Then, the noise levels were measured based on three variables: skid number, vehicle speed, and distance from the classrooms at seven selected points of the main ring road surrounding the university campus. Finally, the finding has shown that the classrooms' locations of the new urban additions, built in the last two decades, were laid out in the prohibited distance of road-traffic noise. In addition to that, it has confirmed that students studying in these classrooms are exposed to noise levels beyond the legislative norms and codes. Further, studying the alternatives used to improve the performance of the education environment in the existing campus of University of Baghdad can be considered in the future research directions.